2017
DOI: 10.1016/j.jaad.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Clinical similarity of biosimilar ABP 501 to adalimumab in the treatment of patients with moderate to severe plaque psoriasis: A randomized, double-blind, multicenter, phase III study

Abstract: ABP 501 was shown to be clinically similar to adalimumab. Safety and immunogenicity were not impacted immediately after single transition (adalimumab to ABP 501).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(84 citation statements)
references
References 12 publications
4
80
0
Order By: Relevance
“…Comparative data regarding neutralising ADAs were reported in six studies (all clinical); none of which observed any clinically relevant [60, 96, 97, 104] or significant [61, 73, 96] differences between groups. No studies reported any treatment failure related to the development of ADAs.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative data regarding neutralising ADAs were reported in six studies (all clinical); none of which observed any clinically relevant [60, 96, 97, 104] or significant [61, 73, 96] differences between groups. No studies reported any treatment failure related to the development of ADAs.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, clinical studies assessing the efficacy and safety of adalimumab biosimilars performed so far either have not assessed multiple switches or, at best, have included one single switch from the reference medicine to the biosimilar. 15,16 As biological medicines are typically large, complex glycoprotein molecules produced in living organisms, it is impossible to produce an identical copy. As a result, inherent batch-to-batch variability exists for all biologics, even between different batches of the same reference medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The results support emerging data on switching, from clinical trials and registries in many indications. 2,3,16,[23][24][25][26] For example, in the recent NOR-SWITCH study, single switches from reference to biosimilar infliximab in patients with Crohn disease, ulcerative colitis, ankylosing spondylitis, rheumatoid arthritis, PsA and psoriasis were not inferior to continued treatment with the reference medicine, and safety and immunogenicity were similar between patients who switched or continued treatment. 23 The present study and analysis of switching data have some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…A phase I, single‐dose study of ABP 501 in healthy adults demonstrated similar pharmacokinetics to that of adalimumab . To establish similarity between ABP 501 and adalimumab in clinical efficacy, safety and immunogenicity, two phase III studies were conducted: one in patients with moderate‐to‐severe rheumatoid arthritis (NCT01970475) and the other in patients with moderate‐to‐severe plaque psoriasis (NCT01970488) …”
mentioning
confidence: 99%
“…This phase III, randomized, double‐blind, 52‐week study was designed to demonstrate clinical similarity in the efficacy, safety and immunogenicity of ABP 501 compared with adalimumab for the treatment of patients with moderate‐to‐severe plaque psoriasis. Results for the primary efficacy and safety end points at week 16 have previously been reported . Here we report the 52‐week efficacy and safety results from this study including data from patients who underwent a single transition from adalimumab to ABP 501.…”
mentioning
confidence: 99%